2016
DOI: 10.1016/j.joca.2015.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Aging and age related stresses: a senescence mechanism of intervertebral disc degeneration

Abstract: Intervertebral disc (IVD) degeneration is a complicated process that involves both age-related change and tissue damage caused by multiple stresses. In a degenerative IVD, cellular senescence accumulates and is associated with reduced proliferation, compromised self-repair, increased inflammatory response, and enhanced catabolic metabolism. In this review, we decipher the senescence mechanism of IVD degeneration (IVDD) by interpreting how aging coordinates with age-related, microenvironment-derived stresses in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
314
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 371 publications
(321 citation statements)
references
References 109 publications
3
314
0
4
Order By: Relevance
“…However, variability in the basal levels of senescence (and proliferation capacity) between donors was present, as these differed with respect to age, pathology, degeneration grade and mixture of NP and AF tissue. Senescence in vivo is not only associated with the degree of disc degeneration [45], but also varies between NP and AF [20]. Furthermore, pro-inflammatory cytokines may trigger cell senescence [45], and these may not only be secreted by resident IVD cells, but also by invading immune cells found predominantly in IVD herniation samples [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, variability in the basal levels of senescence (and proliferation capacity) between donors was present, as these differed with respect to age, pathology, degeneration grade and mixture of NP and AF tissue. Senescence in vivo is not only associated with the degree of disc degeneration [45], but also varies between NP and AF [20]. Furthermore, pro-inflammatory cytokines may trigger cell senescence [45], and these may not only be secreted by resident IVD cells, but also by invading immune cells found predominantly in IVD herniation samples [46].…”
Section: Discussionmentioning
confidence: 99%
“…Senescence in vivo is not only associated with the degree of disc degeneration [45], but also varies between NP and AF [20]. Furthermore, pro-inflammatory cytokines may trigger cell senescence [45], and these may not only be secreted by resident IVD cells, but also by invading immune cells found predominantly in IVD herniation samples [46]. Despite the differences in basal levels of senescence and proliferation capacity stemming from disparities in patient characteristics, we were able to show that microgravity and TRPC channel inhibition both increased cell senescence and decreased cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Intervertebral disc degeneration is a disease that is positively correlated with aging [37, 38]. With the increase in the population of elderly people around the world, disc degeneration has attracted more and more attention [39].…”
Section: Discussionmentioning
confidence: 99%
“…NP cell senescence is also a classical cellular feature in degenerative disc NP tissue, which decreases NP matrix content and ultimately attenuates disc function [6]. Previous epidemiological studies reported that DM patients exhibit a higher incidence of disc degenerative diseases than patients without DM, and DM patients with disc degenerative diseases are much younger than non-DM patients [4, 7, 8].…”
Section: Introductionmentioning
confidence: 99%